Mobility Management for Businesses - Guasco, Clement (Proceedings from the Annual Transport Conference at Aalborg University, 2012)
There is today an undisputed superiority of cars on any other means of transportation, both practically and psychologically. However, the reliance on cars as main means of transportation has led to a number of social and environmental problems. Mobility Management aims at managing the way people fulfil their mobility needs so that they rely less on their cars and start using alternatives such as bicycles and public transport. This article analyses the possibility to use businesses as vectors for introducing Mobility Management within social practices in Denmark in the light of the recent developments in this area.